Evaluating efficiency of nondestructive detection of flaws in concrete - Sutan, N. Mohamed; Jaafar, M.S. (Springer, 2003)
Tests have been performed to assess feasibility of using the impact-echo method (IEM) and ultrasonic pulse velocity method (UPVM) in detecting flaws and evaluating their depths on the early stage of a concrete structure's service life. Five reinforced concrete (RC) slabs of grades 25, 30, 40, and 50 with fabricated voids at known locations were studied on the 3rd, 7th, 14th, and 28th day. The results were compared to estimate the accuracy of both methods and their efficiency. Both methods detected flaws in the tested samples on the early stages of their operation. Depth measurements of flaws by IEM, however, are more accurate. Results of our tests indicate that both methods can be used in determining depths of flaws in concrete and in performing on-site tests. The accuracy of both methods proved to be better in tests of stronger concretes, and the detection probability ranged from 51.81 to 99.8% after aging during 3 to 28 days under full load, respectively.